2013
DOI: 10.1111/jch.12058
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Hypertensive Crises Who Are Admitted to a Coronary Care Unit: Clinical Characteristics and Outcomes

Abstract: Patients with hypertensive crises, especially hypertensive emergencies, require immediate admittance to an intensive care unit for rapid blood pressure (BP) control. The authors analyzed the prevalence of hypertensive crisis, the clinical characteristics, and the evolution of patients with hypertensive emergencies and urgencies. Patients were divided into 3 groups according to their BP values: group I, predominant systolic hypertension ( ! 180/ 119 mm Hg); group II, severe systolic and diastolic hypertension (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…It affects approximately 1 billion individuals globally [1]. HTN ranked as the leading single factor for Global Burden of Diseases, most notably in Sub-Saharan Africa and South Asia regions where a substantial proportion of the world's population resides.…”
Section: Introductionmentioning
confidence: 99%
“…It affects approximately 1 billion individuals globally [1]. HTN ranked as the leading single factor for Global Burden of Diseases, most notably in Sub-Saharan Africa and South Asia regions where a substantial proportion of the world's population resides.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, 25% of patients with hypertensive crisis admitted to the coronary care unit will present with this diagnosis. 10 These patients characteristically have a history of heart failure with preserved ejection fraction. 11 In distinction, neither patient reported here had such a history, and both presented with a decline in their EF from the mid-60% range to less than 50%.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study with hypertensive crisis patients who were admitted to a coronary care unit, researchers found that the overall mortality was 3.7%. In patients with hypertensive emergency, the mortality was higher (4.6%) compared with patients with hypertensive urgencies (0.8%) (23). Despite the different prognosis between patients with two entities, other researchers tried to find prognostic factors of major adverse cardiac or cerebrovascular events (MACCE) defined as a composite of myocardial infarction, unstable angina, hypertensive crisis, pulmonary edema, stroke, or transient ischemic attack.…”
Section: Prognosismentioning
confidence: 99%